New insights into the proximal tendons of adductor longus, adductor brevis and gracilis. Issue 12 (17th October 2011) - Davis, J A; Stringer, M D; Woodley, S J
Abstract : Objective: The adductor muscles are implicated in the pathogenesis of groin strain, but the proximal morphology of this muscle group is poorly defined. The purpose of this study was to investigate the detailed anatomy of the entheses and proximal musculotendinous junctions (MTJs) of adductor longus (AL), adductor brevis (AB) and gracilis. Methods: The adductors were dissected bilaterally in 10 embalmed cadavers (7 females, mean age at death 79 years (range 57–93 years)), focusing on the type of enthesis, and architecture of the proximal tendons and MTJs. Histology was used to determine if the entheses contained fibrocartilage and to semiquantitatively assess the vascularity of each proximal tendon. Results: All entheses were fibrocartilaginous. The proximal tendons of AB and gracilis were fused, forming a common tendinous insertion in all specimens. AL and AB both contained extensive intramuscular tendons of variable length (AL 11.1 ± 1.5 cm; AB 5.4 ± 1.1 cm); this has not been recorded previously. The vascularity of AL and AB tendons decreased significantly towards the enthesis (p < 0.05), and their entheses were significantly less vascular than that of gracilis (p < 0.05). Conclusions: The proximal anatomy of AL, AB and gracilis is more complex than previously described. The arrangement and fusion of these muscles, their fibrocartilaginous entheses and differences in vascularity of their proximal tendons may be important anatomical considerations in the pathogenesis and pattern of adductor-related groin pain.